Optimal management of fatigue in patients with systemic lupus erythematosus: a systematic review - Yuen HK; Cunningham MA (Dove Medical Press, 2014)
Hon K Yuen,1 Melissa A Cunningham2 1Department of Occupational Therapy, School of Health Professions, University of Alabama at Birmingham, Birmingham, AL, 2Division of Rheumatology and Immunology, Department of Medicine, Medical University of South Carolina, SC, USA Abstract: Among the host of distressing pathophysiological and psychosocial symptoms, fatigue is the most prevalent complaint in patients with systemic lupus erythematosus (SLE). This review is to update the current findings on non-pharmacological, pharmacological, and modality strategies to manage fatigue in patients with SLE and to provide some recommendations on optimal management of fatigue based on the best available evidence. We performed a systematic literature search of the PubMed and Scopus databases to identify publications on fatigue management in patients with SLE. Based on the studies reported in the literature, we identified nine intervention strategies that have the potential to alleviate fatigue in patients with SLE. Of the nine strategies, aerobic exercise and belimumab seem to have the strongest evidence of treatment efficacy. N-acetylcysteine and ultraviolet-A1 phototherapy demonstrated low-to-moderate levels of evidence. Psychosocial interventions, dietary manipulation (low calorie or glycemic index diet) aiming for weight loss, vitamin D supplementation, and acupuncture all had weak evidence. Dehydroepiandrosterone is not recommended due to a lack of evidence for its efficacy. In addition to taking treatment efficacy and side effects into consideration, clinicians should consider factors such as cost of treatment, commitments, and burden to the patient when selecting fatigue management strategies for patients with SLE. Any comorbidities, such as psychological distress, chronic pain, sleep disturbance, obesity, or hypovitaminosis D, associated with fatigue should be addressed. Keywords: health-related quality of life, vitality, systemic lupus erythematosus, clinical effectiveness, rheumatology